Analysis of the Impact of Singapore Government Policies on the Development of Halal Tourism (2020–2024) - Yuda Ardiansyah; Aulia Srifauzi (Dauliyah Journal of Islamic and International Affairs, 2026)
The development of halal tourism has become one of the strategic policies of the Singapore government in responding to global tourism competition and the increasing mobility of Muslim international travelers. This study aims to analyze the impact of Singapore’s government policies on halal tourism development using the perspective of Liberalism in International Relations. Liberalism views states as rational actors that promote cooperation, policy openness, and the use of institutions to achieve mutual benefits. This research employs a qualitative method through a literature review of government policy documents, tourism reports, and publications from international organizations. The findings indicate that Singapore’s halal tourism policy is implemented through the provision of Muslim-friendly facilities, a credible halal certification system, and inclusive tourism promotion. These policies have contributed to enhancing Singapore’s attractiveness to Muslim tourists, strengthening the tourism sector, and expanding regional and international tourism cooperation. Overall, the development of halal tourism in Singapore reflects liberal principles that emphasize cooperation, institutional roles, and mutual gains in international relations.